THE FAST FOURIER TRANSFORM AND THE CONTINUOUS WAVELET TRANSFORM ANALYSIS OF THE NORMAL AND PATHOLOGICALS PHONOCARDIOGRAM SIGNALS (Sciences & Technology. A, exactes sciences, 2002)
This paper present the applications of  the fast Fourier transform (FFT) and the continuous wavelet  transform (CWT) to analyse the normal and pathological cases of the phonocardiogram signals  (PCG). The wavelet transform provides more features of  the PCG signals that will help physicians to obtain qualitative  and quantitative measurements of the time-frequency PCG signal characteristics. The frequency content of such a signal is shown to be  determined by the FFT  without difficulties.